Effect of Minor Populations of NS5A and NS5B Resistance-Associated Variants on HCV Genotype-3 Response to Daclatasvir plus Sofosbuvir, with or without Ribavirin. Issue 3 (April 2017) - McPhee, Fiona; Hernandez, Dennis; Zhou, Nannan
Background: Treatment of hepatitis C virus (HCV) genotype 3 (GT3) is a medical priority. All-oral treatment of HCV GT3 with daclatasvir (DCV) and sofosbuvir (SOF), with or without ribavirin (RBV), is recommended by several treatment guidelines. The impact of HCV minority populations at amino acid positions in NS5A and NS5B associated with drug resistance on response to DCV+SOF±RBV was assessed in SOF-naive and SOF-experienced HCV patients. Methods: The presence of baseline NS5A or NS5B polymorphisms was assessed in 227 and 167 HCV-GT3-infected patients, respectively, from four clinical studies of DCV+SOF±RBV. Polymorphisms were identified at a sequencing detection threshold of ≥10%, and at ≥1% by next-generation sequencing (NGS) for a subset. Results: No SOF resistance-associated polymorphisms were detected at baseline. Among 58 patients with prospective baseline sequencing data at ≥10% and ≥1%, detectable NS5A substitutions at A30 (A30K/R/S/T/V), S62 (S62A/F/K/L/T) or Y93H were 38% more prevalent at ≥1% compared with ≥10% (55% [32/58] versus 41% [24/58] of patients), although sustained virological response (SVR) in patients with these substitutions remained the same at both sequencing thresholds (88%). Only one additional Y93H was detected at ≥1%; the patient achieved SVR. In two virological failures with baseline Y93H, a minority S62L substitution at baseline was enriched from <20% to ≥95% at failure. Treatment-emergent minority populations (at A30, L31, P32, P58 and E92) observed by NGS in four virological failures became undetectable by week 24 post-treatment. Conclusions: Sequencing at a depth of ≥10% appears to be sufficient to predict HCV GT3 response to DCV+SOF±RBV.